(3TQM aQGFO GdCUhd GdeYQha HGdQSGFd ddCfUGQjs - (3GdfLaj, , GHf cGTa GdZWGA, Ydj Hf eMeO QVG Hf ehSi, J HYO (B1354(3g`s ((3HNW GdeDdas)
(3ChdgG (B:s
(3bhdg dJMUjd GdGYJbGO, CQGO HGdGYJbGO Cj GdbhHd GdbdHj hGdJOjf GdbdHj, bhdg dgPg GdeSFdI, Cj dhLhH GdYde HPdc, bhdg RjGOI GdfXQ Ydi GdfXQ GdPj MUd efg GdXfs
(3BNQgG (B:s
(3BNQgG(B: (3dCf Yedge HGdJNjQ aj cJH Gdabg EfeG cGf ef LgI CNHGQ GdJNjQ hcPG Mce HYVge HGdJSGbW hGdQLhY Edi GdCUd aj cJH Gdabg jXgQ ef COdJge ajgG Cfg ebJVi faS aUGQ ef GdNHQjf dG ef LgI GdCOdI(B.s
(3GdfSNI YHGQI Yf eShOI GdeDdas
(3JHUQI GdeDda (B:s
(3PcQ GdRQcdj haGJg SfI (B1350(3g`, ZjQ Cfg cGf MjG SfI (B1354(3, hab eG PcQg eG PcQ aj fgGjI GdLRA GdYGTQ ef cJGH TQM GdcaGjIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe, L (B5: 19s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3CUhd Gdabgs